Active Learning Teaching and Learning Model of Entrepreneurship Subject at English Education Program of Indonesia University of Education - Amir, Amir; Suryana, Deddy (Universitas Negeri Semarang, 2018)
The awareness to build the relevance between learning methods, modern world development, and characteristics of students are the starting point of this study. World development can directly change the characteristics of students. Due to the facts, educators are required to have an understanding of postmodern education characteristics. The characteristics of postmodern education is student-centred. It can be realized through the implementation of Active Learning (AL) method. This study aims to portray the implementation of AL method in Entrepreneurship subject at English Education program of UPI. The exploration is focused on 3 things: the implementation of AL method, its impact, and student's responses to the use of this learning method. In this study. Qualitative descriptive research design was used as the research method. The subjects of this study are 1 lecturer of the related subject and 51 students of English Education program of 2016/2017 academic year. Based on the analysis, this study came up with 3 conclusions. The first is that AL method implementation is reflected in some efforts created by the lecturer, the assessment, and the AL characteristics. The second is that AL method has a positive impact on students' ability. The third is that students gave positive responses.